Distinct beneficial effect of Sn on the corrosion resistance of Cr–Mo low alloy steel. (10th August 2021) - Sun, Meihui; Yang, Xiaojia; Du, Cuiwei; Liu, Zhiyong; Li, Yong; Wu, Yumin; San, Hongyu; Su, Xiandong; Li, Xiaogang
Graphical abstract: Highlights: The effect of Sn on the corrosion resistance mechanism of Cr-Mo steel is proposed. The addition of Sn can improve the corrosion resistance of the steel matrix. The synergistic effect of Sn, Cr and Mo can improve the stability of the rust layer. The synergistic effect of Sn, Cr and Mo can reduce the risk of localized corrosion. Abstract: In this work, the beneficial effect of Sn addition on the corrosion resistance mechanism of Cr–Mo low alloy steel was studied. Results demonstrated that Sn improves the corrosion resistance of the steel matrix mainly by influencing the microstructural transformation. Sn addition and the synergistic effect of Sn, Cr, and Mo promote the formation of α-FeOOH, SnO2, SnO, Cr(OH)3, and molybdates, lead to the improved protection and stability of the rust layer. This synergistic effect also endows the inner rust layer with cation selectivity, preventing the further penetration of Cl − and inhibiting the localized corrosion of steel.